Budaya Organisasi dan Perubahan dalam Pengembangan Organisasi - Walean, Ronny Hansje (JBE (Journal of Business and Economics); Volume 4 No.1, 2005 JBE UNKLAB, 2005)
Theera of information technology is an are that provides a very big freedom for an organization to develop and to response. The change becomes contant, rapid, and radical so each organization is required to anticipate the changes. The organization enviroment with its zharacteristic changes, requires the organization culture is a very important factor to study more deeply by each organizational and each needs to realize that culture is a very import factor success and the survival of the organization. The pupose of this paper is to encourage an organazation to realize how crucial it is to consider the important of culture and its changes for the success of an organization particularly in this era, the era of information technology.